2006
DOI: 10.1093/rheumatology/kel137
|View full text |Cite
|
Sign up to set email alerts
|

Bone oedema predicts erosive progression on wrist MRI in early RA--a 2-yr observational MRI and NC scintigraphy study

Abstract: The degree of local synovial inflammation at baseline, evaluated by dynamic and static MRI and quantitative NC scintigraphy, is closely related to the progression of wrist joint erosions during the first 2 yrs of the disease. Furthermore, at follow-up, if no persistent clinical response is achieved, these imaging methods may help to predict future erosiveness and help in clinical therapeutic decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 31 publications
3
36
0
11
Order By: Relevance
“…the strongest independent predictor of radiological progression [15]. Palosaari et al found a close relationship between bone-marrow edema and subsequent articular erosions in their 2-year study [16]. Ostgendorf et al studied the diagnostic efficacy of duplex ultrasound, positron emission tomography (PET), and mini-arthroscopy and found this combination useful for the early detection of pathomorphological abnormalities, as well as for the prediction of prognosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…the strongest independent predictor of radiological progression [15]. Palosaari et al found a close relationship between bone-marrow edema and subsequent articular erosions in their 2-year study [16]. Ostgendorf et al studied the diagnostic efficacy of duplex ultrasound, positron emission tomography (PET), and mini-arthroscopy and found this combination useful for the early detection of pathomorphological abnormalities, as well as for the prediction of prognosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Mori et al [12] proposed the use of MIP images reconstructed from transverse, T1-weighted, contrast-enhanced MR images after fat saturation and suggested the introduction of a new scoring system for MIP imaging of the hand in rheumatoid arthritis. Usually, reproducible scoring systems such as the Outcome Measures in RA Clinical Trials (OMERACT) include the assessment of bone erosions, bone marrow oedema and synovitis volume [13], which are considered the key factors for predicting erosive progression [14]. According to the rheumatoid arthritis magnetic resonance imaging system (RAMRIS) criteria, bone erosions have to be detectable in two, preferably axial and coronal, image planes, whereas bone marrow oedema is best depicted upon non-contrast-enhanced, T2-weighted All analyses were performed including all joints and tendon sheaths images after fat saturation, preferably in the coronal plane [15].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that MRI pathology (synovitis, bone erosions or, most often, BME) of the wrist and MCP joints at disease onset in early RA predicts radiographic erosions [108,[126][127][128][129][130][131][132][133][134]. Some looked at the short-term predictive value of MRI after 1 year [108,126,128,130,131], whereas other studies had 2 [128,132], 3 [134], 5 [133], 6 [127], or 10 years [129] of follow-up.…”
Section: Prognosticationmentioning
confidence: 99%
“…Some looked at the short-term predictive value of MRI after 1 year [108,126,128,130,131], whereas other studies had 2 [128,132], 3 [134], 5 [133], 6 [127], or 10 years [129] of follow-up. All studies found MRI to be a highly significant predictor of radiographic erosions.…”
Section: Prognosticationmentioning
confidence: 99%